The politics of masculinity in the absence of work. (2nd October 2021) - Ray, Raka
ABSTRACT: This paper is an attempt to draw attention to subaltern men – to the costs they are paying in a new global economy, and to the costs that society may well pay for misrecognizing those costs. With a specific focus on India, it highlights the creation of the powerful relationship of masculinity to breadwinning, the range of individual and collective responses to the loss of the ability to be a breadwinner, and ends with pointing to the possibility of different political outcomes and possibilities of ethical existence for these men in these uncertain times.